Development of Energy Saving Multi-Fuel Cooking Stove - Garcia, Jesus; Bajet, Jr., Manuel A. (JPAIR Multidisciplinary Research, 2013)
The Philippines is typical of many developing countries where the majority ofthe population has low income. With the present economic crisis happening dueto the increase of oil prices, housewives are very much worried in budgeting familyexpenditures. They find hard to budget the day to day needs of the family. Thus,the need to design and develop a low consuming, multiple feed cooking stove, yetcomparably performs with liquefied petroleum gas (LPG), kerosene and electric stove,would somehow ease the day to day expenditure. Energy Saver Multi-Fed CookingStove was structured and made up of scrap iron bars sheet and a pipe welded together.It has a chimney and an ash tray. Multi- Fuel in the sense that it can be fuelledwith firewood, charcoal like corn cobs, tobacco stalks, and others which were usuallyburned when the farmers lack knowledge in making use into fertilizer. Qualitativetesting was done in cooking different food was done to identify the cooking fuelconsumption. Using firewood is more economical in cooking with rice, vegetabledishes, boiling of fruits and root crops. While cooking meat and frying fish, charcoalis also more economical. In cooking different foods, it is significantly different fromone another of fuel material. This implies that all the fuel materials are significantlydifferent in terms of cooking different foods. Furthermore, cooking different foods issignificantly different in all cooking stoves like LPG, kerosene, clay and electric stove.
Keywords: Conserve Energy Develop Multi-feed Cooking Stove; Vigan City; Ilocos Sur; Philippines